Gambaran Kelelahan Kerja Pada Operator Alat Berat Bagian Coal Handling di PT. X - Putri, Ulfatun Nadiyah; Sahri, Moch; Sunaryo, Merry; Ayu, Friska (Poltekkes Kemenkes Jambi, 2025)
Background: A heavy equipment operator is someone who is skilled at operating vehicles such as excavators and bulldozers. Work fatigue is a condition of weakening of activities and physical exhaustion from doing work. Several factors of work fatigue include work factors (work shifts, work load and work period), individual factors (age, education, work nutrition). Method: This research uses quantitative descriptive with analytical design and a cross-sectional approach. The population and sample were 24 workers, the sampling technique used total sampling. Results: Statistical test results using crosstab showed that many complaints of work fatigue were obtained from the results of mild fatigue as many as 22 respondents (91.7%) and moderate fatigue 2 respondents (8.3 %). Conclusion: on work fatigue factors including age, education, nutritional status, length of work, workload and work shifts influence the occurrence of fatigue.